Isolated tuberculous epididymo-orchitis: an unusual presentation of tuberculosis - Vishnu Prasad Shenoy; Shashidhar Viswanath; Annet D'Souza; Indira Bairy; Joseph Thomas (Journal of Infection in Developing Countries)
Isolated epididymo-orchitis is an unusual presentation of tuberculosis. A case of bilateral epididymitis and right-sided orchitis with scrotal involvement in a 38-year-old male patient is presented. Strong clinical suspicion of tuberculous etiology was confirmed by appropriate investigations of epididymal biopsy. The patient improved clinically with antitubercular therapy.